Evaluating Large Patch-Tolerant and Cold Hardy Zoysiagrass Germplasm in the Transition Zone - Mingying Xiang; Jack D. Fry; Megan M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2018)
AZoysia japonicagenotype, TAES 5645, that exhibited partial resistance to large patch in preliminary studies conducted by our collaborators at Texas A&M University, was used as a breeding parent at Texas A&M and crossed with 22 cold hardy zoysiagrasses, resulting in 2,858 progeny. These progeny were evaluated for cold hardiness and agronomic traits (establishment rate, overall quality, spring green up, leaf texture, and genetic color) in Manhattan, KS; West Lafayette, IN; and Dallas, TX; from 2012 to 2014. This report focuses on the Manhattan, KS, results. From this work, 60 progeny were identified for further evaluation in larger plots. In fall 2016, ‘Meyer’ (42% of plot area affected) had more large patch than all zoysiagrass progeny (0 to 23%). In spring 2017, Meyer had 33% large patch, higher than most progeny. Among this group of experimental zoysiagrasses, there appear to be promising progeny that have good winter hardiness, resistance to large patch, and improved turf quality characteristics. Data collection is ongoing.
Keywords: Disease; turfgrass; large patch